Success Training for Academic Resiliency: An Advising Intervention Program for Undergraduate Students on Probation - Liu, Charles; Bruner, Justin; Ammigan, Ravichandran (Journal of Interdisciplinary Studies in Education, 2022)
In this paper, we examine how Success Training for Academic Resiliency (STAR) Lite, an advising intervention program, influenced undergraduate students to overcome academic probation into achieving good academic standing. We use descriptive quantitative methods to assess the impact of program participation for 194 undergraduate students on academic probation at a large public university in the Midwestern region of the United States. We found that 153 students who participated in the STAR Lite program returned to good academic standing after one semester of intervention, in comparison to 41 undergraduate students who did not participate and did not improve academically. The implication of the findings suggests that students participating in all or extra of the intervention program components overall improved their academic status from probation to good standing.